DEVELOPMENT OF INTERACTIVE E-MODULES OF ISLAMIC RELIGIOUS EDUCATION FOR CHILDREN/PENGEMBANGAN E-MODUL INTERAKTIF MATA PELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK - Laili Mas’udah; Umi Salamah; Kasuwi Saiban (Al-Mudarris: Journal Of Education, 2022)
The development of the field of information and technology is very rapid. The world of education cannot be separated from change. The teaching materials needed are currently in electronic form (e-modules), because they can convey more concrete messages through videos and interactive quizzes, so learning is more fun. The research objective is the development, feasibility and implementation of interactive e-modules for PAI subjects in children.The type of research R and D refers to Borg and Gall: 1) research and information gathering, 2) planning, 3) product development, 4) initial field test, 5) initial product revision, 6) further field test, 7) operational production revision, 8) operational field test and 9) field test. The results showed that the assessments of: 1) material experts 92%, very decent category; 2) 85% of media experts are classified as very decent. Random trials, 39 students in small-scale trials and 166 students in large-scale trials showed, the aspects of use were very interesting, access was very easy, very helpful in learning. The usefulness aspect is very clear, the instructions and presentation of the material are clear. Aspects of presentation of questions and appropriate material. Appearances, interesting practice questions, e-module quizzes are effective and very effective in helping to improve understanding. Thus, this interactive e-module is very feasible and can be implemented as a PAI learning media for children.